Meningkatkan Kinerja Guru Melalui Supervisi Akademik Di SDN Kauman II Tahun Pelajaran 2022/2023 - Rochim, Abdul (Science and Education Journal (SICEDU), 2022)
This study aims to improve teacher performance through continuous academic supervision at SDN Kauman II, Baureno District, Bojonegoro Regency. The research method used is a school action research (PTS) approach. This research was carried out in the second semester of the 2021/2022 academic year, precisely in April 2022. The results of the research and discussion can be concluded that there is an increase in teacher performance through the academic supervision of the Kauman II State Elementary School for the 2021/2022 academic year. This is evidenced by the results of school action research (cycle 1) and guidance by the principal until cycle 2, the average value of teacher performance is 74.8 to 87,1. Improving Teacher Performance through academic supervision of the Kauman II State Elementary School for the 2021/2022 academic year with Principal Guidance, is able to increase activities in coaching activities that support improving teacher performance such as training, upgrading, workshops, Teacher Working Groups (KKG) which are useful and can help teachers to more easily understand the concept of the role and function of teachers so that improving teacher performance in teaching in schools can run well, and thus improving teacher performance can be improved.